Syndrome and outcome of antibody‐negative limbic encephalitis. (21st May 2018) - Graus, F.; Escudero, D.; Oleaga, L.; Bruna, J.; Villarejo‐Galende, A.; Ballabriga, J.; Barceló, M. I.; Gilo, F.; Popkirov, S.; Stourac, P.; Dalmau, J.
Abstract : Background and purpose: The aim was to report the clinical characteristics of 12 patients with limbic encephalitis (LE) who were antibody‐negative after a comprehensive immunological study. Methods: The clinical records of 163 patients with LE were reviewed. Immunohistochemistry on rat brain, cultured neurons and cell‐based assays were used to identify neuronal autoantibodies. Patients were included if (i) there was adequate clinical, cerebrospinal fluid (CSF) and magnetic resonance imaging information to classify the syndrome as LE, (ii) magnetic resonance images were accessible for central review and (iii) serum and CSF were available and were confirmed negative for neuronal antibodies. Results: Twelve (7%) of 163 LE patients [median age 62 years; range 40–79; 9 (75%) male] without neuronal autoantibodies were identified. The most frequent initial complaints were deficits in short‐term memory leading to hospital admission in a few weeks (median time 2 weeks; range 0.5–12). In four patients the short‐term memory dysfunction remained as an isolated symptom during the entire course of the disease. Seizures, drowsiness and psychiatric problems were unusual. Four patients had solid tumors (one lung, one esophagus, two metastatic cervical adenopathies of unknown primary tumor) and one chronic lymphocytic leukemia. CSF showed pleocytosis in seven (58%) with a median of 13 white blood cells/mm 3 (range 9–25). Immunotherapy included corticosteroids, intravenous immunoglobulins and combinations of both drugs or with rituximab. Clinical improvement occurred in six (54%) of 11 assessable patients. Conclusions: Despite the discovery of new antibodies, 7% of LE patients remain seronegative. Antibody‐negative LE is more frequent in older males and usually develops with predominant or isolated short‐term memory loss. Despite the absence of antibodies, patients may have an underlying cancer and respond to immunotherapy. Abstract : Click here for the corresponding questions to this CME article.